Good news reduces trust in government and its efficacy: The case of the Pfizer/BioNTech vaccine announcement. - Shaun P Hargreaves Heap; Christel Koop; Konstantinos Matakos; Aslı Unan; Nina Weber (PLoS ONE)
The announcement of Pfizer/BioNTech's COVID-19 vaccine success on November 9, 2020 led to a global stock market surge. But how did the general public respond to such good news? We leverage the unexpected vaccine announcement to assess the effect of good news on citizens' government evaluations, anxiety, beliefs and elicited behaviors in the US and the UK. While most outcomes were unaffected by the news, trust in government and elected politicians (and their competency) saw a significant decline in both countries. As the news did not concern the governments, and the governments did not have time to act on the news, our results suggest that the decline of trust is more likely explained by the psychological impact of good news on reasoning style. In particular, we suggest two possible styles of reasoning that might explain our results: a form of motivated reasoning and a reasoning heuristic of relative comparison.